SUBJEKT I NACIONALNE IDEOLOŠKE PARADIGME U POSTKOMUNISTIČKOM KONTEKSTU (NA PRIMJERU MODERNDORFEROVA ROMANA PREDMESTJE) (Филологические заметки, 2019)
This paper analyzes confrontation of the subject with ideological forms in post-communism, Slovenian reality in novel Predmestje by Moderndorfer inparticular. We approach relations among symbolization, subjectivity and the anchoring point as a place of identification. Freud’s psychoanalysis, Lacan’s psychoanalytic theories, Althusser’s theory on ideology and the conceptual system from Žižek’s study Sublime Object of Ideology are applied to the study as compatible methodological apparatuses.